L'école primaire au Sénégal : éducation pour tous, qualité pour certains - Fatou Niang (Les éditions de la Maison des sciences de l'Homme, 2014)
Since the 1990's (Jomtien Conference), there is a broad international consensus on the need to add to the goal of quantitative expansion of education, the imperative of quality improvement. However, combining these two objectives can be difficult in countries under severe financial and human constraints. In the case of Senegal, the article shows that educational authorities tend to arbitrate in favour of expanding access to education, an option that has affected the quality and created inequalities of quality of education between different sections of the society. The paper present the emergence of the concept of quality of education and its various representations through international conferences and scientific and technical literature as well as how the concept was taken into account in the Senegalese public policies. Then through qualitative survey data in urban and rural areas in Senegal, it examine the state of the quality of education in the schools surveyed beyond the discourse of public policy; and thus, show how the policies of recruitment of teachers, the use of special classes, the construction and maintenance of school infrastructures and the development of private schools, have increased enrolment while creating different norms in terms of quality standards for populations and disparities between schools and classes.